ACTIVE LISTENING: ADAB MENERIMA ILMU PADA MAHASISWA PSIKOLOGI (PERSPEKTIF PSIKOLOGI ISLAM) - Imanti, Vera; Kusnulia Rosita; Intan Wahyu Istiqomah (Asosiasi Psikologi Islam (API) Himpsi, 2021)
The implementation of Islamic noble character is to receive knowledge. Lack of attitudes to acquire knowledge should be overcome by preparing college students with attitudes to acquire knowledge. One of them is – having active listening skills. This skill has positive impacts on interpersonal communication and creates a harmonious relationship. This skill can be improved by applying it to receive knowledge. It is the reason why psychological students are prepared with this skill. It allows them to listen and analyze a problem of a client. This research aims to find out the description of active listening (the attitudes of receiving knowledge by college students). This research is qualitative, involving 28 college students taken by random sampling technique. The data were collected with an opened questionnaire distributed by Google form and interview. The data analysis applied descriptive data analysis. The findings showed that the students’ active listening skills would be easily applied when an individual had a better understanding of obtaining knowledge and could apply the skill. The active listening skill had to be trained and developed by students, especially psychological students. It would be necessary when they engaged with clients and analyzed their problems. It was essential to pay attention in applying active listening while promoting the attitudes of receiving knowledge, especially in terms of physics, mentality, empathy, and open-mind. Active listening would emerge if all people applied the attitudes of acquiring knowledge. Keywords : attitudes to receive knowledge, active listening, psychological students